What lies beneath? Hepatitis E virus surveillance in Belgian wastewater suggests hidden trends in community circulation - Noor Ul Hudda; Marie De Smedt; Raphael Janssens; Inge Roukaerts; Koenraad Van Hoorde; Veronik Hutse; Hadrien Maloux; Bavo Verhaegen; Arno Furquim d'Almeida; Naomi De Roeck; Michael Peeters; Steven Van Gucht; et al. (Science of The Total Environment, 2026)

Behavioral and pharmacological investigation of putative self-medicative natural materials used by wild chimpanzees and mountain gorillas - Fabien Schultz; Inken Dworak-Schultz; Florian Wald; Lisa Grohs; Tabitha Iker; Godwin Anywar; Gladys Kalema-Zikusoka; Matthew McLennan; Catherine Hobaiter; Lewis Marquez; Sunmin Woo; Luc Pieters; et al. (Phytochemistry Letters, 2025)

Pyrazolyl amide-chalcones conjugates: Synthesis and antikinetoplastid activity - Devesh S. Agarwal; Richard M. Beteck; Dorien Mabille; Guy Caljon; Lesetja J. Legoabe (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
A series of novel pyrazolyl amide-chalcones conjugates was synthesized in five steps and evaluated against a range of medically important kinetoplastid parasites including Trypanosoma cruzi , Trypanosoma brucei brucei , Trypanosoma brucei rhodesiense and Leishmania infantum . In addition, the series was also tested for in vitro cytotoxicity activity against human lung fibroblasts and primary mouse macrophages. Among all synthetised compounds, 9b was found to be the most active against T. b. brucei with an IC 50 value of 0.51 ± 0.06 μM. Against T. b. rhodesiense , 9n was found to be the most potent with an IC 50 value of 0.46 ± 0.07 μM. While against L. infantum , 9a was found to be most active with an IC 50 value of 7.16 ± 1.88 μM. Based on the results and SAR, further modifications will be carried out to increase potency. Graphical Abstract

Synthesis and in vitro biological activity of chalcone derivatives as potential antiparasitic agents - Koketso J. Setshedi; Richard M. Beteck; Kayhan Ilbeigi; Dorien Mabille; Guy Caljon; Lesetja J. Legoabe (Medicinal Chemistry Research, 2024)
Kinetoplastids are a group of flagellated protozoans including medically important parasites of the genus Trypanosoma and Leishmania . The corresponding diseases have afflicted humans for centuries. In an effort to combat kinetoplastid infections, a set of 21 chalcones was synthesized and evaluated for their in vitro anti-protozoal efficacy against Trypanosoma brucei , Trypanosoma brucei rhodesiense , Trypanosoma cruzi , and Leishmania infantum . To ensure safety, these compounds underwent a selectivity evaluation by assessing toxicity against a human lung fibroblast cell line. Compound K4 exhibited remarkable and selective trypanocidal activity against T. b. brucei with IC 50 value of 0.31 ± 0.27 µM and T. b. rhodesiense with IC 50 value of 0.96 ± 0.86 µM. Compound K9 also showed significant trypanocidal activity against T. b. brucei (IC 50 : 0.45 ± 0.14 µM) and T. b. rhodesiense (IC 50 : 0.93 ± 0.51 µM). In both compounds, electron withdrawing groups are appended to the styrenyl moiety.

Correction to: Preparation and Characterization of Nanostructured Lipid Carriers for Improved Topical Drug Delivery: Evaluation in Cutaneous Leishmaniasis and Vaginal Candidiasis Animal Models - Amina Riaz; Sarah Hendrickx; Kimberley Elbrink; Guy Caljon; Louis Maes; Naveed Ahmed; Filip Kiekens; Gul Majid Khan (AAPS PharmSciTech, 2020)

Preparation and Characterization of Nanostructured Lipid Carriers for Improved Topical Drug Delivery: Evaluation in Cutaneous Leishmaniasis and Vaginal Candidiasis Animal Models - Amina Riaz; Sarah Hendricks; Kimberley Elbrink; Caljon Guy; Louis Maes; Naveed Ahmed; Filip Kiekens; Gul Majid Khan (AAPS PharmSciTech, 2020)